Effects of unmatched longitudinal joints and pavement markings on the lateral position of vehicles - Manepalli Subhash, Vikranth (Kansas State University, 2007)
Motorists generally follow the guidance provided by the pavement markings while traveling on roads. Under certain circumstances, construction joints may be necessary in concrete pavements, which are generally designed to be coincident with the pavement markings. At some locations, however, the construction joints may not exactly match the pavement markings. These situations may create confusion in the minds of drivers, which may lead them to follow joints instead of the markings. In the absence of detailed studies on this topic, an effort was made in the present study to evaluate the effects of unmatched longitudinal construction joints and pavement markings on the lateral position of vehicles. Sites having the characteristics of unmatched longitudinal construction joints and pavement markings were identified, and detailed data were collected at one of the sites. Video camera technique was used for capturing the movements of vehicles along the test site for longer durations. The video tapes were later reduced in the laboratory to extract necessary information. The distance to the right side of the vehicles from right curb of the road, the type of vehicle, presence of vehicles in the adjacent lane, weather and light conditions, and the movement of the vehicles immediately after traversing the section of the road having unmatched longitudinal construction joints and pavement markings were the main parameters observed while reducing the data. Two surveys were also conducted for gathering the opinions of some practitioners and engineers on the issue. Statistical analyses were carried out using t-tests to evaluate if there were differences. Several comparisons were made for different types of vehicles based on various conditions. The analysis results indicated that there was a statistically significant difference between the actual and expected distances to the center-line of vehicles, implying that the lateral position of vehicles may have been affected by the joints. A model was also developed to determine the lateral position of the vehicles by considering the parameters used in the analysis. Based on the survey results and analysis of field data, it was found that the lateral position of vehicles may have been affected by the unmatched joints and pavement markings.
Keywords: Unmatched longitudinal joints and pavement markings; Driver behavior; Engineering, Civil (0543)